Hans Raun Iversen, Grundtvig, folkekirke og mission - Pedersen, Kim Arne (Grundtvig-studier, 2009)
Hans Raun Iversen, Grundtvig, the Evangelical Lutheran Church in Denmark and mission Reviewed by Kim Arne Pedersen